Comparison of the activities of penicillin G and new beta-lactam antibiotics against clinical isolates of Bacteroides species. - Aldridge, K E (1984)
MICs were determined for 218 clinical isolates of Bacteroides by a broth microdilution method. Imipenem was the most active antibiotic tested. Azlocillin, mezlocillin, and cefoxitin had comparable activities, with resistance among members of the B. fragilis group and B. capillosus. Ceftizoxime was the most active cephalosporin tested. Members of the B. fragilis group showed high levels of resistance to cefotetan and ceftazidime. Resistance to penicillin G varied from 0 to 14%.